Autologous transplant vs. CAR-T therapy in patients with DLBCL treated while in complete remission - Mazyar Shadman; Kwang W. Ahn; Manmeet Kaur; Lazaros Lekakis; Amer Beitinjaneh; Madiha Iqbal; Nausheen Ahmed; Brian Hill; Nasheed M. Hossain; Peter Riedell; Ajay K. Gopal; Natalie Grover; et al. (Blood Cancer Journal, 2024)
Abstract In patients with relapsed DLBCL in complete remission (CR), autologous hematopoietic cell transplantation (auto-HCT) and CAR-T therapy are both effective, but it is unknown which modality provides superior outcomes. We compared the efficacy of auto-HCT vs. CAR-T in patients with DLBCL in a CR. A retrospective observational study comparing auto-HCT (2015–2021) vs. CAR-T (2018–2021) using the Center for International Blood & Marrow Transplant Research registry. Median follow-up was 49.7 months for the auto-HCT and 24.7 months for the CAR-T cohort. Patients ages 18 and 75 with a diagnosis of DLBCL were included if they received auto-HCT (n = 281) or commercial CAR-T (n = 79) while in a CR. Patients undergoing auto-HCT with only one prior therapy line and CAR-T patients with a previous history of auto-HCT treatment were excluded. Endpoints included Progression-free survival (PFS), relapse rate, non-relapse mortality (NRM) and overall survival (OS). In univariate analysis, treatment with auto-HCT was associated with a higher rate of 2-year PFS (66.2% vs. 47.8%; p < 0.001), a lower 2-year cumulative incidence of relapse (27.8% vs. 48% ; p < 0.001), and a superior 2-year OS (78.9% vs. 65.6%; p = 0.037). In patients with early (within 12 months) treatment failure, auto-HCT was associated with a superior 2-year PFS (70.9% vs. 48.3% ; p < 0.001), lower 2-year cumulative incidence of relapse (22.8% vs. 45.9% ; p < 0.001) and trend for higher 2-year OS (82.4% vs. 66.1% ; p = 0.076). In the multivariable analysis, treatment with auto-HCT was associated with a superior PFS (hazard ratio 1.83; p = 0.0011) and lower incidence of relapse (hazard ratio 2.18; p < 0.0001) compared to CAR-T. In patients with relapsed LBCL who achieve a CR, treatment with auto-HCT is associated with improved clinical outcomes compared to CAR-T. These data support the consideration of auto-HCT in select patients with LBCL achieving a CR in the relapsed setting.